ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL OPERASI BENTUK ALJABAR KELAS VIII MTS - Suspita, Baiq Lina; Masjudin, Masjudin (Media Pendidikan Matematika, 2019)
This study aims to describe the difficulty of students in solving problems in the form of algebra clas VIII in terms of 3 indicators, namely (1) difficulty understanding concepts (2) difficulty understanding principles (3) difficulty understanding verbal problems. This type of research is descriptive qualitative research. This research was conducted at Madrsarah Tsanawiyah Darul Hikmah of West Lombok. Data analysis techniques used are dat reduction, data display, and conclusions distribution. The result of the study stated that (1) students ability to understand concept was in the low category. The difficukty in understanding the concept is not being able to define terms. Coefficients, variables, and constants. (2) the ability of students to understand the principle is in the low category. Difficulty in understanding the principle that students are not able to operate the addition, subtraction, multiplication, and division of algebraic forms if the variables are similar and not similar. (3) the ability of student to understand verbal problems is in the low category. The difficulty of student in understanding verbal problems is that students are not able to understand the purpose of questions in the form of stories, student do not understand what is asked in the problem. This show that the ability of student in each indicator is categorized as low.